Highly thermally conductive grout composition and method thereof
Patent Information
- Application Number
- JP2024546055
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-01
- Filing Date
- 2023-01-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-25
AI Technical Summary
【0015】 本発明の主題の様々な目的、特徴、態様、および利点は、同様の数字が同様の構成要素を表す添付の図面の図とともに、好ましい実施形態の以下の詳細な説明からより明らかになるであろう。
Smart Images

Figure 2025505595000001_ABST
Abstract
Description
[Technical Field]
[0001] This application claims priority to co-pending U.S. Provisional Patent Application No. 63 / 305,599, filed February 1, 2022, which is incorporated herein by reference.
[0002] The field of the invention is compositions and methods for heat transfer in geothermal heat recovery, and in particular, compositions with high thermal conductivity that can be deployed / installed in very high temperature wells. [Background technology]
[0003] The background discussion contains information useful in understanding the present invention. No admission is made that any of the information provided herein is prior art or relevant to the presently claimed invention, or that any publication specifically or implicitly referenced is prior art.
[0004] All publications and patent applications herein are incorporated by reference to the same extent as if each individual publication or patent application was specifically and individually indicated to be incorporated by reference. If a definition or use of a term in an incorporated reference contradicts or contradicts the definition of that term provided herein, the definition of that term provided herein shall apply and the definition of that term in the reference shall not apply.
[0005] Geothermal wells have been used to provide heating and cooling systems that transfer heat to and from the earth. In a typical vertical well closed-loop system, two pipes joined by a U-shaped connector at the bottom, forming a continuous casing, are installed vertically in a well drilled into the earth (see U.S. Patent Application Publication No. 2012 / 0247766). This type of system is commonly used for heating and cooling residential and commercial buildings. A conventional clay-based grout mixture is pumped into the well to fill the annular space between the casing and the earth formation. The resulting grout forms a seal to prevent groundwater contamination and to prevent subsurface contamination from above ground. The grout mixture may further include a thermally conductive material to aid in heat transfer between a working fluid in the casing and the target location, and the working fluid may circulate within the well loop to transfer heat to and from a heat exchanger at the surface.
[0006] While such conventional geothermal wells are effective at providing heating and cooling to locations proximate the well (e.g., heat exchangers) through heat transfer, they do not provide sufficient thermal energy to generate electricity using turbine-based power generation systems. To obtain the thermal energy necessary to generate electricity, the well must be significantly deeper than the earth's surface and / or proximate to a known geothermal hot zone (e.g., a crustal plate boundary). However, all or nearly all grout compositions formed from conventional grout mixtures are unable to efficiently transfer increased thermal energy or maintain workability during construction at extreme temperatures (e.g., geothermal temperatures of 300°F at the target location) near the target location (e.g., the geothermal energy source). Among other problems, the high temperatures at the target location almost always result in premature curing of the grout composition and generally fail to provide sufficiently high thermal conductivity, making power generation ineffective or even feasible.
[0007] Certain clay-based grout mixtures containing salt-containing retarders and electrically conductive materials are known (see, e.g., U.S. Pat. No. 9,845,423), but these retarders are generally used to retard the swelling of aqueous swelling clays. Such and other formulations may further include carbon-based additives to enhance thermal conductivity (see, e.g., U.S. Pat. No. 7,452,417). However, such formulations do not provide sufficient workability of the grout mixture during application into wellbore, let alone during application at extreme temperatures (e.g., 300°F).
[0008] As a further known example, as described in U.S. Patent Application Publication No. 2012 / 0247766, a grout composition containing reactive silica, a calcium source, and a carbon additive is provided to form a thermally conductive material for a geothermal heat pump system. Similarly, as described in U.S. Patent Application Publication No. 2007 / 0125274, a thermally conductive material can be included in a cementitious material. Unfortunately, such compositions are also unsuitable for installation in high-temperature formations with formation temperatures sufficient for power generation, as such temperatures cause the composition to harden prematurely, preventing proper installation at the target location in the formation. Additionally, the addition of a thermally conductive material can reduce the pumpability of the composition or even render it unpumpable, particularly when the grout composition is required to have high thermal conductivity.
[0009] Thus, although various compositions for geothermal grouts are known in the art, all or nearly all of them suffer from several drawbacks. Accordingly, there remains a need for compositions and methods for pumpable, highly thermally conductive grouts that can be placed in formations having temperatures suitable for power generation. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] U.S. Patent Application No. 2012 / 0247766 [Patent Document 2] U.S. Patent No. 9,845,423 [Patent Document 3] U.S. Patent No. 7,452,417 [Patent Document 4] U.S. Patent Application No. 2007 / 0125274 Summary of the Invention [Problem to be solved by the invention]
[0011] The present subject matter is directed to various compositions for high thermal conductivity grouts and methods for producing pumpable slurries that form such high thermal conductivity grouts. The high thermal conductivity grouts are formed from grout mixtures that can be utilized for grouting applications in heat harvesting wells, particularly closed-loop geothermal system wells for geothermal power generation. The high thermal conductivity grouts advantageously improve the heat transfer per unit length of the well. This improved heat transfer results in greater thermal energy capture in the working fluid, increasing the revenue of the power-generating well. [Means for solving the problem]
[0012] In one aspect of the present subject matter, a grout mixture of a high thermal conductivity grout composition includes a cementitious material, a retarder, and a high thermal conductivity material. In some embodiments, the workability of the grout composition is improved from the use of a retarder, which allows for placement of the grout in a well even under extreme temperature conditions (e.g., geothermal temperatures of at least 300°F at the target location). Without being bound by theory, the inventors contemplate, for example, that the retarder is present in an amount effective to delay the setting of the grout mixture at a target location having a target temperature of at least 300°F for at least two hours. Furthermore, without being bound by theory, the inventors also contemplate that the high thermal conductivity material is present in an amount effective to cause the grout mixture to have a thermal conductivity of at least 1 W / m°K as it sets at the target location.
[0013] In various embodiments, the grout mixture includes a high thermal conductivity material such as graphite, silicon carbide, etc., and possibly a conventional cementitious material such as Portland cement, calcium aluminate cement, etc. The grout mixture preferably has a large volume fraction of solid high thermal conductivity material to provide a high thermal k (high thermal conductivity constant) for the grout available within the well. To this end, the inventors further envision that having a high thermal conductivity grout on the outside of the casing string will significantly increase the thermal efficiency of the well.
[0014] In another aspect of the present subject matter, a geothermal well is formed in an earth formation containing a plurality of fractures at least partially filled with a high thermal conductivity material (which may or may not be the same as those described above). The high thermal conductivity material in the fractures exchanges heat with the high thermal conductivity grout. The high thermal conductivity material in the fractures may be selected from the group consisting of graphite powder, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, silicon carbide, and combinations thereof. The at least partially filled fractures increase the surface area available for thermal energy, thereby providing more heat to the working fluid in the well.
[0015] Various objects, features, aspects and advantages of the present subject matter will become more apparent from the following detailed description of preferred embodiments, taken in conjunction with the accompanying drawing figures in which like numerals represent like elements. [Brief explanation of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic diagram illustrating an embodiment of a geothermal well including a wellbore during installation of a pumpable slurry. [Figure 2] FIG. 2 is a schematic diagram illustrating the geothermal well embodiment of FIG. 1 after the pumpable slurry has hardened. DETAILED DESCRIPTION OF THE INVENTION
[0017] The inventors have discovered various highly thermally conductive grout compositions and methods for producing pumpable slurries. Advantageously, the grout compositions and slurries have properties that allow the slurry to be pumped to a target location, even when the target location is at a significant depth and the target location temperature exceeds 300°F (the geothermal temperature of the target location). In other words, the hardening of the slurry at the target location is delayed long enough for the slurry to reach the target location, even at significant depths and at very high temperatures. Furthermore, upon hardening at the target location, a highly thermally conductive grout is formed, enabling heat extraction (e.g., using a closed-loop heat extraction system) for power generation in an economical and continuous manner.
[0018] In one embodiment, the high thermal conductivity grout composition comprises a grout mixture including a cementitious material, a retarder, and a high thermal conductivity material. In some embodiments, workability is improved by the use of a retarder, which allows the grout composition to be placed in a well even under extreme temperature conditions (e.g., geothermal temperatures of at least 300°F at the target location). Accordingly, the inventors contemplate that the retarder be present in an amount effective to delay the setting of the grout mixture at a target location having a target temperature of at least 300°F, at least 400°F, or at least 500°F for at least two hours. Furthermore, it is generally preferred that the high thermal conductivity material be present in the mixture in an amount effective to provide a thermal conductivity of at least 1 W / m°K, at least 4 W / m°K, or at least 10 W / m°K when the grout mixture sets at the target location (i.e., hardens to at least 80% of its final hardness).
[0019] The cementitious material may be any cementitious material suitable for use in underground works, including, but not limited to, hydraulic cement, non-hydraulic cement, or a combination thereof. Hydraulic cement hardens through a process of hydration, a chemical reaction that produces an insoluble hydrate (e.g., calcium hydroxide), which occurs regardless of the water content of the cement (e.g., hydraulic cement may harden under consistently wet conditions). Thus, hydraulic cement can harden regardless of the water content of a particular underground formation. Suitable hydraulic cements include, but are not limited to, Portland cement, Portland cement blends (e.g., Portland blast furnace slag cement, expansive cement, etc.), non-Portland hydraulic cements (e.g., persulfate cement, calcium aluminate cement, high-magnesium cement, etc.), or combinations thereof. Suitable non-hydraulic cements include, but are not limited to, hydrated lime, gypsum, lime gypsum, and any combination thereof. In certain embodiments, the cementitious material is a hydraulic cement, such as Portland cement or calcium aluminate cement.
[0020] The cementitious material may be present in the grout mixture of the high thermal conductivity grout composition in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the cementitious material may be present in the grout mixture in an amount not exceeding 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the cementitious material may be present in the grout mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight, based on the total weight of the grout mixture.
[0021] The retarder may be any compound capable of delaying the setting of the grout mixture of the high thermal conductivity grout composition at the target location for at least 2 hours, at least 3 hours, at least 4 hours, at least 5 hours, at least 6 hours, or at least 7 hours. The target location may have a target temperature (geothermal temperature at the target location) of at least 300°F, at least 350°F, at least 400°F, at least 450°F, at least 500°F, at least 550°F, at least 600°F, at least 650°F, or at least 700°F.
[0022] For example, suitable retarders for use in contemplated grout mixtures include salts containing cations and anions, polymers, silicates, partially hydrolyzed polyvinyl acetate, polyacrylamide, partially hydrolyzed polyacrylamide, polyalkylene glycols (e.g., polybutylene glycol, polyethylene glycol, polypropylene glycol, etc.), polyalkylene alcohols, polyalkylene alkoxylates, polyalkylene oligomers, polyalkylene polymers, polyalkylene copolymers, cationic oligomers or polymers, acids, potassium salts (e.g., potassium fluoride, potassium chloride, potassium chlorate, potassium bromide, potassium iodide, potassium iodate, potassium acetate, potassium citrate, potassium formate, potassium nitrate, dibasic potassium phosphate, monobasic potassium phosphate, potassium sulfate, potassium disulfate, potassium carbonate, potassium dichromate, potassium ferrate, etc.), ammonium salts, sodium salts, iron salts, aluminum salts These include, but are not limited to, iron salts, aluminum salts, phosphonium salts, polyaminopolyamide-epichlorohydrin resin, diallyldimethylammonium chloride, polydiallyldimethylammonium chloride, aminoethylethanolamine, diethylenetriamine, triethylenetetramine, diethanolamine, triethanolamine, polyvinylpyrrolidone, potassium silicate, potassium carbonate, tribasic potassium phosphate, or combinations thereof.
[0023] In some embodiments, the salts include cations and anions, such as, but not limited to, at least one of lithium, potassium, sodium, hydronium, ammonium, calcium, magnesium, quaternary amines, magnesium, calcium, strontium, barium, titanium, cesium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, aluminum, zirconium, and any combination thereof, and anions, such as, but not limited to, at least one of chloride, bromide, nitrate, iodide, hydroxide, nitrite, hexafluoroantimonate, hexafluoroarsenate, hexafluorophosphate, propionate, lactate, tartrate, phosphate, phosphonium, borate, silicate, sulfate, acetate, aluminate, chromate, dichromate, permanganate, chlorate and perchlorate, formate, or combinations thereof.
[0024] In other embodiments, the retarder may comprise a cationic oligomer or polymer. Suitable cationic oligomers or polymers include, but are not limited to, at least one monomer comprising imine, alkyleneimine, ethyleneimine, propyleneimine, amine, ethyleneamine, organic amine, quaternary amine, acrylamide, methacrylamide, putrescine, cadaverine, spermidine, spermine, diethylenetriamine, tetramethylenediamine, triethylenetetramine, tetraethylenepentamine, diallyldimethylammonium chloride, (2-methacryloyloxyethyl)trimethylammonium chloride, vinylpyrrolidone, any derivative thereof, any salt thereof, or a combination thereof.
[0025] Silicates suitable for use as retarders of the present disclosure can be of any type suitable for such use, including silicates, oligomeric silicates, polymeric silicates, etc. Examples of suitable silicates include, but are not limited to, alkaline earth metal silicates, alkaline earth metal silicates, and any combination thereof, such as sodium silicate, calcium silicate, potassium silicate, sodium metasilicate, calcium metasilicate, potassium metasilicate, etc.
[0026] It should be understood that, depending on the type of retarder used, the retarder can be present in the grout mixture of the high thermal conductivity grout composition in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the retarder can be present in the grout mixture in an amount of 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight or less, based on the total weight of the grout mixture. Alternatively, the retarder can be present in the grout mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight, based on the total weight of the grout mixture. Viewed another way, the retarder preferably has a composition and is present in an amount sufficient to delay the hardening of the grout composition into a grout for at least 2 hours, or at least 3 hours, or at least 4 hours, or at least 5 hours (and even more) at target temperatures of at least 300°F, at least 350°F, at least 400°F, at least 450°F, at least 500°F, at least 550°F, at least 600°F, at least 650°F, and even higher (geothermal temperatures at the target location).
[0027] As will be appreciated, the high thermal conductivity material is used to improve the thermal conductivity of the high thermal conductivity grout formed from the grout mixture, and therefore improve the ability of the geothermal well loop to extract heat during operation. Suitable high thermal conductivity materials include, but are not limited to, graphite, sand, quartz silica, carbon nanotubes, graphene, boron nitride, brass, brass alloys, chromium-nickel steel, carbon steel, stainless steel, transition metals (e.g., copper, cadmium, cobalt, gold, silver, iridium, iron, molybdenum, nickel, platinum, zinc, etc.), transition metal alloys (e.g., copper alloys, cadmium alloys, zinc alloys, etc.), copper alloys, cadmium alloys, cobalt alloys, gold alloys, silver alloys, iridium alloys, iron alloys, molybdenum alloys, nickel alloys, platinum alloys, zinc alloys, etc.), post-transition metals (e.g., lead, tin, etc.), post-transition metal alloys (e.g., lead alloys, tin alloys, etc.), alkaline earth metal alloys (e.g., beryllium alloys, magnesium alloys, etc.), or combinations thereof. In certain embodiments, the high thermal conductivity material is graphite powder, exfoliated graphite, flake graphite, pyrolytic graphite, desulfurized petroleum coke, carbonaceous materials such as graphene, fly ash, copper powder, aluminum nitride, silicon carbide, and combinations thereof.
[0028] In some embodiments, the high thermal conductivity material can be present in the grout mixture of the high thermal conductivity grout composition in an amount sufficient to provide the desired thermal conductivity for the high thermal conductivity grout for geothermal wells. Thus, and depending on the specific type of material, the high thermal conductivity material can be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, or even more by weight, based on the total weight of the grout mixture. Alternatively, the high thermal conductivity material can be present in the grout mixture in an amount of up to 60%, 50%, 45%, 40%, 35%, 20%, 15%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the high thermal conductivity material may be present in the grout mixture in an amount of about 1 to about 20 wt.%, about 5 to about 15 wt.%, or about 7 to about 13 wt.%, based on the total weight of the grout mixture.
[0029] Thus, in some embodiments, a high thermal conductivity grout formed from a grout mixture of a high thermal conductivity grout composition comprising a high thermal conductivity material has a thermal conductivity of at least 0.5 British thermal units per foot per hour per degree Fahrenheit (BTU / hr·ft·°F), at least 0.578 BTU / hr·ft·°F (1 W / m°K), at least 1.0 BTU / hr·ft·°F, at least 2.0 BTU / hr·ft·°F, at least 2.312 BTU / h r·ft·°F (4W / m°K), at least 3.0 BTU / hr·ft·°F, at least 5.0 BTU / hr·ft·°F, at least 5.782 BTU / hr·ft·°F (10W / m°K), at least 7 BTU / hr·ft·°F, at least 10 BTU / hr·ft·°F, at least 14 BTU / hr·ft·°F, at least 16 BTU / hr·ft·°F, or at least 20 BTU / hr·ft·°F, or even higher. Alternatively, a high thermal conductivity grout formed from a grout mixture containing a high thermal conductivity material has a thermal conductivity of 30 BTU / hr·ft·°F or less, 25 BTU / hr·ft·°F or less, 20 BTU / hr·ft·°F or less, 18 BTU / hr·ft·°F or less, 16 BTU / hr·ft·°F or less, 14 BTU / hr·ft·°F or less, 12 BTU / hr·ft·°F or less, or 10 BTU / hr·ft·°F or less.
[0030] The grout mixture of the high thermal conductivity grout composition may further include at least one functional agent. The functional agent can be used to modify the rheological properties of the grout mixture in response to various stimuli, such as temperature, pressure, contact with another material, or a combination thereof. Thus, suitable functional agents include plasticizers, surfactants, organic polymers, silica fillers, clays, and combinations thereof.
[0031] In some embodiments, a plasticizer may be present in the grout mixture of the high thermal conductivity grout composition to improve workability for ease of installation. In various embodiments, the term "plasticizer" refers to a substance that improves the flowability of the grout mixture, thereby improving the workability of the grout mixture or allowing the grout mixture to be produced with less water while maintaining equivalent workability. Suitable plasticizers include, but are not limited to, polycarboxylic ether plasticizers, phthalate plasticizers, terephthalate plasticizers, sulfonamide plasticizers, benzoate plasticizers, phosphate plasticizers, or combinations thereof.
[0032] In some embodiments, and depending on the type of plasticizer, the plasticizer may be present in the grout mixture of the high thermal conductivity grout composition in an amount sufficient to impart the desired workability to the grout mixture. For example, the plasticizer may be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the plasticizer may be present in the grout mixture in an amount of up to 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the plasticizer may be present in the grout mixture in an amount of about 1 to about 20% by weight, about 5% to about 15% by weight, or about 7% to 13% by weight, based on the total weight of the grout mixture.
[0033] In a further embodiment, a surfactant may be present in the grout mixture of the high thermal conductivity grout composition to improve the wetting of the grout mixture. Thus, contemplated surfactants include, but are not limited to, nonionic surfactants, anionic surfactants, cationic surfactants, zwitterionic surfactants, or combinations thereof.
[0034] Suitable nonionic surfactants include alkoxylates (e.g., alkoxylated nonylphenol condensates such as poly(oxy-1,2-ethanediyl), alpha-(4-nonylphenyl)-omega-hydroxy-branched), alkylphenols, ethoxylated alkylamines, ethoxylated oleates, tall oil, ethoxylated fatty acids, alkyl polyglycosides, These include, but are not limited to, sorbitan esters, methyl glucoside esters, amine ethoxylates, diamine ethoxylates, polyglycerol esters, alkyl ethoxylates, polypropoxylated and / or polyethoxylated alcohols, linear alcohol alkoxylates, dodecylbenzenesulfonate derivatives, linear nonyl-phenols, dioxane, ethylene oxide, polyethylene glycol, ethoxylated castor oil, polyoxyethylene nonylphenol ether, tetraethylene glycol dodecyl ether, ethylene oxide, decylamine oxide, dodecylamine oxide, alkylamine oxides, ethoxylated amides, alkoxylated fatty acids, alkoxylated alcohols (e.g., lauryl alcohol ethoxylate, ethoxylated nonylphenol), ethoxylated fatty amines, ethoxylated alkylamines (e.g., cocoalkylamine ethoxylate), any derivatives thereof, and any combination thereof. As used herein, the term "derivative" refers to any compound prepared from one of the compounds, for example, by replacing one atom in the named compound with another atom or group of atoms, or by rearranging two or more atoms in the compound.
[0035] Suitable anionic surfactants include alpha sulfo fatty acid methyl ester salts. sulfonate), hydrolyzed keratin, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, alkyl ether sulfate, sodium 4-(1'heptylnonyl)benzenesulfonate, sodium dioctyl sulfosuccinate, sodium octylbenzenesulfonate, sodium hexadecyl sulfate, sodium laureth sulfate, quaternary ammonium compounds (e.g., trimethyl coco ammonium chloride, trimethyl tallow ammonium chloride, dimethyl dicoco ammonium chloride, etc.), cetylpyridinium chloride, alkyl ester sulfonates, alkyl ether sulfonates, alkyl ether sulfates, alkali metal alkyl sulfates, alkyl sulfonates, alkyl aryl sulfonates, sulfosuccinates, alkyl disulfonates, alkyl aryl disulfonates, alkyl disulfates, alcohol polypropoxylated sulfates, alcohol polyethoxylated sulfates, any derivatives thereof, or any combination thereof.
[0036] Suitable zwitterionic surfactants include, but are not limited to, alkylamine oxides, alkylbetaines, alkylamidopropylbetaines, alkylsulfobetaines, alkylsultaines, dihydroxyalkylglycinates, alkylamphoacetates, phospholipids, alkylaminopropionic acids, alkyliminomonopropionic acids, alkyliminodipropionic acids, dipalmitoyl-phosphatidylcholine, amine oxides, betaines, modified betaines, alkylamidobetaines (e.g., cocoamidopropylbetaine), and any combination thereof.
[0037] Additionally, surfactants that may exhibit viscoelastic properties include, but are not limited to, sulfosuccinates, taurates, amine oxides (e.g., amidoamine oxides), ethoxylated amides, alkoxylated fatty acids, alkoxylated alcohols, ethoxylated fatty amines, ethoxylated alkylamines, betaines, modified betaines, alkylamidobetaines, quaternary ammonium compounds, alkyl sulfates, alkyl ether sulfates, alkyl sulfonates, ethoxylated esters, ethoxylated glycoside esters, alcohol ethers, any derivatives thereof, and any combinations thereof.
[0038] Generally, the surfactant may be present in the grout mixture of the high thermal conductivity grout composition in an amount sufficient to achieve a desired surface tension of the grout mixture. Thus, the surfactant may be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the surfactant may be present in the grout mixture in an amount of up to 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the surfactant may be present in the grout mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight, based on the total weight of the grout mixture.
[0039] Organic polymers may be present in the grout mixture of the high thermal conductivity grout composition to improve various properties of the grout mixture (e.g., control of rheological parameters or suppression of heat of hydration). Therefore, suitable organic polymers include, but are not limited to, natural compounds, synthetic compounds, or combinations thereof. Non-limiting examples of suitable natural compounds include cold-water soluble polysaccharides and polysaccharide ethers, such as polysaccharides, e.g., cellulose ethers, starch ethers (amylose and / or amylopectin and / or their derivatives), guar ethers, dextrins, or combinations thereof. Non-limiting examples of suitable synthetic compounds include protective colloids, e.g., one or more polyvinylpyrrolidones and / or polyvinyl acetates, polyvinyl alcohols, melamine formaldehyde sulfonates, naphthalene formaldehyde sulfonates, block copolymers of propylene oxide and ethylene oxide, styrene-maleic acid and / or vinyl ether-maleic acid copolymers.
[0040] In some embodiments, the organic polymer may be present in the grout mixture of the high thermal conductivity grout composition in an amount sufficient to impart a desired amount of properties to the grout mixture. The organic polymer may be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the organic polymer may be present in the grout mixture in an amount of up to 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the organic polymer may be present in the grout mixture in an amount of about 1% to about 20%, about 5% to about 15%, or about 7% to 13% by weight, based on the total weight of the grout mixture.
[0041] Clays may be present in the grout mixture of the high thermal conductivity grout composition to modify the flow properties of the grout mixture. Suitable clays include smectite family clays, palygorskite-sepiolite phyllosilicate family clays, kaolinite-serpentine family clays, nontronite, bentonite, hectorite, attapulgite, fluormica, montmorillonite, beidellite, saponite, sepiolite, kaolinite, illite, cation exchanged versions thereof, or combinations thereof.
[0042] Of the suitable smectite group clays, including nontronite, montmorillonite, saponite, hectorite, and beedelite, other smectite group clays suitable for use as aqueous swelling clays in the present disclosure include, but are not limited to, ariettite, ferrosaponite, sauconite, stevensite, suinefordite, volkonskoite, yahontovite, and any combination thereof. Suitable clays of the palygorskite-sepiolite phyllosilicic acid family include, but are not limited to, attapulgite, tuppersautite, windhaukite, yaufortierite, falcondite, ferrisepiolite, raufrinite, and any combination thereof. Suitable clays from the kaolinite-serpentine family of aqueous swelling clays include, but are not limited to, kaolinite, greenalite, flypontite, halloysite, dickite, lizardite, manandonite, nacrite, cronstedtite, clinochrysotile, chrysotile, nepiite, odinite, webskiite, pecoraite, orthochrysotile, parachrysotile, caryopilite, brindleite, berthierine, amesite, antigorite, boehmite, and any combination thereof.
[0043] In some embodiments, clay may be present in the grout mixture of the high thermal conductivity grout composition in an amount sufficient to impart a desired amount of physical properties to the grout mixture. The clay may be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the clay may be present in the grout mixture in an amount of up to 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the clay may be present in the grout mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight, based on the total weight of the grout mixture.
[0044] The grout mixture of the high thermal conductivity grout composition may also include various additives, such as insulating materials, dispersants, aggregates, or combinations thereof. The additives may modify the thermodynamic properties of the grout mixture, provide a high thermal conductivity grout, or further modify the rheological properties of the grout mixture. Other additives include sodium chloride to improve mixability, viscoelastic surfactants and / or polymers to offset thermal thinning and suspension of solids after placement, fluid loss additives, and accelerators such as calcium chloride.
[0045] Insulating materials may be present in the grout mix of the high thermal conductivity grout composition to modify the thermal conductivity of the resulting high thermal conductivity grout. This is counterproductive to high thermal conductivity materials, but may be desirable for some geothermal wells near the surface to minimize heat transfer outside the well. Suitable insulating materials may be solid particles with low thermal conductivity. Specific examples of insulating materials suitable for use in the grout mix include, but are not limited to, glass (e.g., glass spheres), diatomaceous earth, polyurethane, polyurethane foam, polystyrene, perlite, fiberglass, cork, wood, straw, rock wool, mineral fiber, cellulose, and any combination thereof.
[0046] In some embodiments, the insulating material may be present in the grout mixture of the high thermal conductivity grout composition in an amount effective to impart a desired amount of thermal insulation to the grout mixture. The insulating material may be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the insulating material may be present in the grout mixture in an amount of 20% by weight or less, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the insulating material may be present in the grout mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight, based on the total weight of the grout mixture.
[0047] Dispersants may be present in the grout mix of the high thermal conductivity grout composition as thinners and deflocculants to reduce the viscosity of the final grout fluid and thereby extend the set time of the resulting high thermal conductivity grout, but without being bound by such theory. In some embodiments, dispersants include, but are not limited to, acid derivatives, salts of acid derivatives, phosphates, sodium carbonate, polymeric or monomeric sodium silicate complexes (e.g., sodium metasilicate, water glass, etc.), lignite compounds, and low molecular weight polymers, soaps, surfactants, sulfonates, or combinations thereof.
[0048] Acid derivatives that can be used as dispersants in grout mixtures include, but are not limited to, tannic acid derivatives, citric acid derivatives (e.g., citrate), humic acid derivatives, phosphoric acid derivatives, disodium hydrogen phosphate, trisodium phosphate, dihydrogen phosphate, quebracho, quebracho derivatives, sulfomethylated quebracho, sulfomethylated quebracho derivatives, alkylated quebracho, alkylated quebracho derivatives, naphthalene sulfonic acid condensed with formaldehyde, and any combination thereof. Salts of these acid derivatives can also be suitable as dispersants (e.g., sodium salts of acid derivatives), including, but not limited to, sodium humate, sodium phosphate, sodium citrate, sodium tannate, and the like, and any combination thereof. Phosphates suitable for use as dispersants in the grout additive control package described herein include, but are not limited to, sodium polyphosphate, tetrasodium polyphosphate, sodium tripolyphosphate, sodium hexametaphosphate, sodium acid pyrophosphate, sodium metaphosphate, sodium hexametaphosphate, and any combination thereof. Suitable lignite compounds include, but are not limited to, lignosulfonates, alkali lignosulfonates (e.g., alkaline earth metal lignosulfonates such as sodium, potassium, or calcium), acrylic lignosulfonates, causticized lignite, causticized leonardite, iron lignosulfonates, chromium lignosulfonates, iron-chromium lignosulfonates, transition metal lignosulfonates (e.g., zirconium lignosulfonates, titanium lignosulfonates, etc.), sulfoalkylated lignite, or combinations thereof.
[0049] Examples of suitable low molecular weight polymers include polyacrylates, alkali salts of polyacrylic acid, poly(sulfonated styrene-co-maleic anhydride), poly(acrylic acid-co-vinyl sulfonic acid), alkali salts of polymethacrylates, polyacrylamido-2-acrylamido-2-methylpropanesulfonic acid, the sodium salt of polyacrylamido-2-acrylamido-2-methylpropanesulfonic acid, polymers made from sulfonated condensed naphthalenesulfonic acid polymers, polymers of unsaturated dicarboxylic acids, polymers of monoethylenically unsaturated monocarboxylic acids, polymers of ethylenically unsaturated monomers and polyalcohols. Examples of suitable low molecular weight polymers include, but are not limited to, graft polymers of alkylene glycol, allyloxybenzenesulfonate polymers, alkylated polymeric salts of allyloxybenzenesulfonic acid, terpolymers of tetrahydrophthalic acid, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid and lignosulfonates, graft copolymers of tetrahydrophthalic acid, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid and lignosulfonates, organosilicon polymers, and the term "low molecular weight polymer" as used herein means a polymer having a molecular weight of less than 1,000,000.
[0050] Suitable soaps that can be used as dispersants include sodium stearate, potassium stearate, ammonium stearate, sodium aurate, potassium aurate, sodium myristate, potassium myristate, sodium ricinoleate, potassium ricinoleate, sodium palmitate, potassium palmitate, calcium caprylate, sodium caprylate, potassium caprylate, 4,7,10,13,16,19-docosahexaenoic acid, 4,7,10,13,16-docosapentaenoic acid, 5,8,11,14,17-eicosanoic acid ... Sapentaenoic acid, 5,8,11,14-eicosatetraenoic acid, 5,8,11-eicosatrienoic acid, 6,9,12,15-octadecatetraenoic acid, 7,10,13,16,19-docosapentaenoic acid, 7,10,13,16-docosatetraenoic acid, 8,11,14,17-eicosatetraenoic acid, 8,11,14-eicosatrienoic acid, behenic acid, capric acid, caprylic acid, cis-11-docosenoic acid, cis-11-eicosenoic acid, cis-11-octadecenoic acid, cis-15-tetracosenoic acid, cis-4-decenoic acid, cis-4-dodecenoic acid, cis -4-Tetradecenoic acid, cis-5-lauroyl acid, cis-5-tetradecenoic acid, cis-6-octadecenoic acid, cis-9-decenoic acid, cis-9-dodecenoic acid, cis-9-eicosenoic acid, cis-9-hexadecenoic acid, cis-9-tetradecenoic acid, cis-tetracosenoic acid, caprylic acid, decenoic acid, dihydroxystearic acid, docosadienoic acid, docosahexaenoic acid, docosapentaenoic acid, dotriacontanoic acid, eicosadienoic acid, eicosanoic acid, eicosapentaenoic acid, eicosatetraenoic acid, eicosatrienoic acid, eicosenoic acid, erucic acid, heptadeca The carboxylic acid may include, but is not limited to, oleic acid, heptadecenoic acid, hexacosanoic acid, hexadecadienoic acid, hexadecenoic acid, lauric acid, linoleic acid, linolenic acid, myristic acid, nonadecanoic acid, nonanoic acid, octacosanoic acid, octadecatetraenoic acid, octadecatrienoic acid, oleic acid, palmitic acid, pentadecanoic acid, pentadecenoic acid, pentatriacontanoic acid, ricinoleic acid, stearic acid, tetracosanoic acid, tetradecenoic acid, tetratriacontanoic acid, tricontanoic acid, tridecanoic acid, tritriacontanoic acid, or a combination thereof.
[0051] Sulfonates suitable for use as dispersants include, but are not limited to, melamine sulfonate condensed with formaldehyde, sulfonated styrene maleic anhydride copolymer, sulfonated vinyl toluene maleic anhydride copolymer, sodium naphthalene sulfonate condensed with formaldehyde, sulfonated acetone condensed with formaldehyde, interpolymers of acrylic acid, allyloxybenzene sulfonate, allyl sulfonate, or combinations thereof.
[0052] In some embodiments, the dispersant may be present in the grout mixture of the high thermal conductivity grout composition in an amount sufficient to impart a desired set time to the grout mixture. The dispersant may be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the dispersant may be present in the grout mixture in an amount of up to 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the dispersant may be present in the grout mixture in an amount of about 1 to about 20%, about 5% to about 15%, or about 7% to about 13% by weight, based on the total weight of the grout mixture.
[0053] Aggregates may be present in the grout mixture of the high thermal conductivity grout composition as a filler. Non-limiting examples of suitable aggregates include sand. The sand may have an average particle size of 0.1 mm to 2.0 mm. The sand may be present in the grout mixture in an amount of at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the sand may be present in the grout mixture in an amount of no more than 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10% by weight, based on the total weight of the grout mixture. Alternatively, the sand may be present in the grout mixture in an amount of about 1 to about 20% by weight, about 5% to about 15% by weight, or about 7% to about 13% by weight, based on the total weight of the grout mixture.
[0054] A method for producing a pumpable slurry is also provided. The method includes combining a high thermal conductivity grout composition with a large amount of water. The method further includes mixing the water with the high thermal conductivity grout composition, thereby forming a pumpable slurry. Mixing can utilize any method or process, including a static mixer, a rotary mixer, or a recirculating jet mixer. The high thermal conductivity grout composition grout mixture, upon addition of water, has a viscosity that allows the grout mixture to be pumped to a target location having a target temperature.
[0055] In various embodiments, the amount of water is sufficient to produce a slurry density of about 10 to about 20 pounds per gallon, about 12 to about 18 pounds per gallon, or about 14 to about 16 pounds per gallon. Alternatively, the amount of water is sufficient to produce a slurry density of at least 10 pounds per gallon, at least 12 pounds per gallon, at least 14 pounds per gallon, at least 16 pounds per gallon, or 18 pounds per gallon. Alternatively, the amount of water is sufficient to produce a slurry density of 20 pounds per gallon or less, 18 pounds per gallon or less, 16 pounds per gallon or less, 14 pounds per gallon or less, or 12 pounds per gallon or less.
[0056] The pumpable slurry may include water in a weight ratio of water to cementitious material of about 0.01:1 to about 1:1, about 0.2:1 to about 1:1, about 0.3:1 to about 0.8:1, or about 0.4:1 to about 0.6:1. Alternatively, the pumpable slurry may include water in a weight ratio of water to cementitious material of at least 0.01:1, at least 0.2:1, at least 0.3:1, or at least 0.4:1. Alternatively, the pumpable slurry may include water in a weight ratio of water to cementitious material of 1:1 or less, 0.8:1 or less, or 0.6:1 or less.
[0057] The pumpable slurry may have a water content of 1 to 50 gallons / sk, 1 to 40 gallons / sk, 5 to 30 gallons / sk, or 10 to 20 gallons / sk. Alternatively, the pumpable slurry may have a water content of at least 1 gallon / sk, at least 5 gallons / sk, or at least 10 gallons / sk. Alternatively, the pumpable slurry may have a water content of 50 gallons / sk or less, 40 gallons / sk or less, or 30 gallons / sk or less.
[0058] As will be readily appreciated, the high thermal conductivity grout compositions presented herein can be formulated to meet the specific local requirements of a target location for grout placement in the annular space between the wellbore and the casing. It is contemplated that the target location's temperature and pressure, among other parameters, can be simulated on land, and the composition tailored to achieve specific fluidity and set times at the target location. Thus, the final design of any formulation may require the addition of additional retarders and / or adjustments of other additives to control settling of solids in the slurry prior to settling, as can be readily accomplished by one skilled in the art.
[0059] 1 and 2 are schematic diagrams illustrating an embodiment of a geothermal well 10 including a well 12 during installation of a pumpable slurry 14A (FIG. 1) and after curing of a pumpable slurry 14B (FIG. 2). The geothermal well 10 further includes a casing 16 disposed within the well 12 such that an annular space 18 is formed therebetween. The pumpable slurries 14A / 14B are located within the annular space of the well 12. Upon curing, the pumpable slurry 14A forms a highly thermally conductive grout 14B. The casing 16 is most typically part of a structure that forms a continuous circuit for the working fluid circulating therein and, therefore, may have a conduit-within-a-pipe configuration (as exemplarily shown in FIGS. 1 and 2). However, other configurations, which may or may not include heat exchangers and / or heat exchange fins, are also contemplated as suitable for use herein. The geothermal well 10 is formed within an earth formation 20. In various embodiments, the formation 20 includes a plurality of fractures 22 at least partially filled with a high thermal conductivity material 24. The high thermal conductivity material 24 in the fractures 22 exchanges heat with (and may be chemically bonded to) the high thermal conductivity grout 14B in the wellbore 12. As will be readily appreciated, the high thermal conductivity material 24 in the fractures 22 may be the same material as the high thermal conductivity grout 14A / B, although the high thermal conductivity material 24 may also be a separate material. The high thermal conductivity material 24 in the fractures 22 is preferably a cementitious material and includes thermally conductive materials such as graphite powder, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, silicon carbide, and combinations thereof. As such, the high thermal conductivity material 24 may be the same as or similar to the high thermal conductivity grout compositions presented herein. However, as noted above, it should be understood that the high thermal conductivity material 24 need not include a cementitious component.
[0060] In some embodiments, pumpable slurry 14A is directed through annular space 18 of wellbore 12, where pumpable slurry 14A contacts high thermal conductivity material 24 within fracture 22. In further embodiments, pumpable slurry 14A is directed through annular space 18 of wellbore 12, where pumpable slurry 14A also fills fracture 22, thereby forming high thermal conductivity material 24 within the fracture. In further embodiments, placement of the grout composition is preferably (but not required to be) performed in reverse circulation, as shown in FIG. 1 (and is described, for example, in PROCEEDINGS, Thirty-Fifth Workshop on Geothermal Reservoir Engineering, Stanford University, Stanford, California, February 1-3, 2010, which is incorporated herein by reference). In such an embodiment, slurry 14A is delivered to a target location (typically the distal end of the wellbore) through the annular space, with at least a portion of the slurry exiting upward from the target location through inner return conduit 26 (typically through valves or other fluid control structures, such as stinger and flapper valves, not shown). It should be understood that inner return conduit 26 forms a fluid path 28 for the hot working fluid when the power generation system is operational, and the space between casing 16 and inner return conduit 26 forms fluid path 30 that conveys the working fluid to the target location. In this regard, it should be noted that fluid path 30 can also be used to "flush" any residual slurry in inner return conduit 26, as shown in FIG. 2. As will be readily understood, the direction of working fluid from fluid path 30 to 28 can be achieved via valves or other fluid control structures (not shown).
[0061] Upon completion of installation of the closed-loop conduit (formed in part by the casing 16 and inner conduit 26) and grout, the working fluid in the fluid path 30 is now in direct contact with the casing, which is thermally coupled to the surrounding formation 20 via the hardened high thermal conductivity grout composition 14B and the high thermal conductivity material 24 in the fractures. It should be noted, therefore, that when a wellbore contains fractures at least partially filled with high thermal conductivity material, heat extraction is possible along a continuous, thermally conductive path extending distally from the wellbore into the formation and from the formation through the hardened high thermal conductivity grout composition and into the working fluid.
[0062] In light of the above, the inventors have contemplated various methods for placing the high thermal conductivity grout 14B in the well 12. The methods include pumping a pumpable slurry 14A to a target location within the well 12 having a target temperature (geothermal temperature at the target location) of at least 300°F, at least 350°F, at least 400°F, at least 450°F, or at least 500°F. The target location may be at least 500 feet, at least 600 feet, at least 700 feet, at least 800 feet, at least 900 feet, at least 1,000 feet, at least 1,250 feet, at least 1,500 feet, at least 1,750 feet, at least 2,000 feet, at least 2,500 feet, or at least 3,000 feet below ground. As will be readily appreciated, conventional grout compositions are unsuitable for such operations because the harsh temperature conditions and the time required for the slurry to reach the target location would cause these compositions to fully harden before reaching the target location. In the most typical cases, the target location is a dry, hot rock formation, most often with low or no permeability (e.g., intrusive igneous or metamorphic rocks).
[0063] In various embodiments, the target location extends in a substantially vertical direction. As used herein, the term "substantially" means that the target location extends toward the center of the Earth, but may be offset from the center by no more than 15 degrees, no more than 10 degrees, no more than 5 degrees, or no more than 1 degree. It should be understood that a geothermal well 10 can have multiple target locations, and thus can have both target locations that are substantially vertical and target locations that extend in a direction of at least 30 degrees.
[0064] The method further includes curing the pumpable slurry 14A within the annular space 18, thereby forming a high thermal conductivity grout 14B within the wellbore 12. The high thermal conductivity grout 14B exchanges heat with the casing 16 and the formation 20 surrounding the wellbore 12. Most typically, the curing time for the pumpable slurry 14A is at least 2 hours, at least 3 hours, or at least 4 hours at a formation temperature (geothermal temperature at the target location) of at least 300°F, at least 350°F, at least 400°F, at least 450°F, or at least 500°F.
[0065] In various embodiments, the pumpable slurry 14A is provided to a pump (not shown) that pumps the pumpable slurry 14A into the well 12. In certain embodiments, the steps of combining the high thermal conductivity grout composition with water and pumping the pumpable slurry 14A are separated by at least 4 hours, at least 5 hours, or at least 6 hours. In further embodiments, pumping the pumpable slurry 14A into the annular space 18 between the well 12 and the casing 16 displaces fluid within the annular space 18.
[0066] As noted above, and with continued reference to Figures 1-2, in certain embodiments, a secondary conduit 26 defining a return space 28 is disposed within the casing 16. Thus, a second annular space 30 is formed between the casing 16 and the secondary conduit 26. In these and other embodiments, displacing the fluid within the annular space 18 includes removing fluid through the return space 28 using a secondary fluid that travels from the second annular space 30 to the return space 28.
[0067] Referring to FIG. 2 , during operation of the geothermal well 10, the working fluid may enter the closed-loop system through the second annular space 30 and return to the surface through the return space 28. However, it should be understood that the flow of the working fluid may be reversed. As the working fluid passes through the second annular space 30, geothermal energy from the formation is conducted through the highly thermally conductive material 24 in the fractures 22 and the highly thermally conductive grout 14B to the casing 16 through which the working fluid travels within the annular space 30, thereby increasing the temperature of the working fluid. The working fluid thus heated then travels toward the surface through the return space 28. A heat exchanger and turbine-generator (both not shown) may be installed proximate to the geothermal well 10 to utilize the temperature of the working fluid to generate electrical energy. [Example]
[0068] Tables 1-4 list exemplary high thermal conductivity grout compositions suitable for use herein (where %bwoc = weight percent cement, %bwow = weight percent water). However, it should be understood that these compositions are provided merely to illustrate certain aspects of the inventive subject matter and are not intended to limit the scope of the inventive subject matter. For example, while the formulations below use Portland cement, it should be understood that calcium aluminate cement systems (e.g., Halliburton's ThermaLock™ cement or Brookhaven National Lab's Thermal Shock Resistant Cement (TSRC)) are also expressly contemplated, especially when the target location temperature is relatively high (e.g., above 400°C).
[0069] [Table 1]
[0070] [Table 2]
[0071] [Table 3]
[0072] [Table 4]
[0073] In some embodiments, numerical values expressing properties such as amounts and concentrations of ingredients, reaction conditions, and the like, used to describe and claim particular embodiments of the present invention, are understood to be optionally modified by the term "about." As used herein, the terms "about" and "approximately," when referring to a specified measurable value (parameter, amount, temporal duration, etc.), are meant to encompass the specified value and variations therefrom, e.g., variations of ±10% or less, or ±5% or less, or ±1% or less, or ±0.1% or less, to the extent appropriate for practice in the disclosed embodiments. Accordingly, the values referred to by the modifier "about" or "approximately" are themselves specifically disclosed. The recitation of ranges of values herein is intended merely to serve as a shorthand method of individually referring to each individual value falling within the range. Unless otherwise stated herein, each individual value is incorporated herein as if individually set forth herein.
[0074] All methods described herein can be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. Any examples provided herein with respect to specific embodiments, or the use of exemplary language (e.g., "such as"), are intended merely to better illustrate the invention and do not impose limitations on the scope of the otherwise claimed invention. No language in the specification should be construed as indicating any non-claimed element essential to the practice of the invention.
[0075] As used throughout this specification and the claims that follow, the meanings of "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Also, as used herein, the meaning of "in" includes "in" and "on," unless the context clearly dictates otherwise. As used herein, and unless the context clearly dictates otherwise, the term "coupled to" is intended to include both direct coupling (where the two elements coupled to each other contact each other) and indirect coupling (where at least one additional element is disposed between the two elements). Thus, the terms "coupled to" and "coupled with" are used interchangeably.
[0076] It will be apparent to those skilled in the art that many modifications beyond those already described are possible without departing from the inventive concepts herein. Accordingly, the present subject matter is not limited except as by the appended claims. Moreover, in interpreting both the specification and the claims, all terms should be interpreted in the broadest possible manner consistent with the context. In particular, the terms "comprises" and "comprising" should be interpreted as referring to elements, components, or steps in a non-exclusive manner, indicating that a referenced element, component, or step may be present, utilized, or combined with other elements, components, or steps not expressly referenced. When the specification or claims refer to at least one selected from the group consisting of A, B, C, ... and N, the statement should be interpreted as requiring only one element from that group, and not A+N, B+N, etc.
Claims
1. A highly thermally conductive grout composition comprising: a grout mixture including a cementitious material, a retarder, and a highly thermally conductive material; the retarder is present in an amount effective to retard hardening of the grout mixture for at least two hours at a target location having a geothermal target temperature of at least 300° F.; and the high thermal conductivity material is present in an amount effective to have a thermal conductivity of at least 1 W / m°K when the grout mixture hardens at the target location; Grout composition.
2. The composition of claim 1 , wherein the grout mixture further comprises at least one functional agent.
3. The composition of claim 2 , wherein the functional agent is selected from the group consisting of plasticizers, surfactants, organic polymers, silica fillers, and clays.
4. The composition of claim 1 , wherein the cementitious material is a hydraulic cement.
5. 5. The composition of claim 4, wherein the cementitious material is Portland cement or calcium aluminate cement.
6. The composition of claim 1 , wherein the grout mixture further comprises sand having an average particle size of 0.1 mm to 2.0 mm.
7. 10. The composition of claim 1, wherein the retarder is selected from the group consisting of lignosulfonates, phosphonates, sugars, hydroxycarboxylic acids, borates, and salts of Zn, Pb, Cu, Sb, or As.
8. 10. The composition of claim 1, wherein the high thermal conductivity material is selected from the group consisting of graphite powder, exfoliated graphite, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, and silicon carbide.
9. 10. The composition of claim 1, wherein the retarder is present in an amount effective to delay hardening of the grout mixture at a target location having a geothermal target temperature of at least 400°F for at least 2 hours.
10. 10. The composition of claim 1, wherein the retarder is present in an amount effective to delay hardening of the grout mixture at a target location having a geothermal target temperature of at least 500°F for at least two hours.
11. 10. The composition of claim 1, wherein the high thermal conductivity material is present in an amount effective such that, upon curing in situ, the grout mixture has a thermal conductivity of at least 4 W / m°K.
12. 10. The composition of claim 1, wherein the high thermal conductivity material is present in an amount effective such that, upon curing in situ, the grout mixture has a thermal conductivity of at least 10 W / m°K.
13. 13. The composition of any one of claims 1 to 12, wherein the grout mixture has a viscosity that, upon addition of water, enables it to be pumped to the target location having the target temperature.
14. A pumpable slurry comprising an admixture of the high thermal conductivity grout composition of any one of claims 1 to 13 and water.
15. 15. The pumpable slurry of claim 14 having a density of 10 to 20 pounds per gallon.
16. 16. The pumpable slurry of any one of claims 14 to 15, having a water content of from 5 to 30 gal / sk.
17. 1. A method for producing a pumpable slurry, comprising: Combining a high thermal conductivity grout composition according to any one of claims 1 to 13 with a large amount of water; and mixing the water with a highly thermally conductive grout composition to form the slurry, the amount of water being sufficient to produce a slurry density of 10-20 pounds per gallon; A manufacturing method comprising:
18. 20. The method of claim 17, wherein the mixing uses a static mixer, a rotary mixer, or a jet mixer.
19. 19. The method of claim 17 or 18, further comprising the step of: feeding the pumpable slurry to a pump that pumps the slurry into a well.
20. 20. The method of claim 19, wherein the steps of combining the high thermal conductivity grout with water and pumping the slurry are separated by at least 4 hours.
21. 1. A method of placing a high thermal conductivity grout in a wellbore, comprising: placing a casing in the wellbore such that an annular space is formed therebetween; Pumping the pumpable slurry of any one of claims 14 to 16 to a target location within the well having a geothermal target temperature of at least 300°F; and allowing the pumpable slurry to harden within the annular space, thereby forming the high thermal conductivity grout within the wellbore, the high thermal conductivity grout exchanging heat with the casing and the formation surrounding the wellbore, and a hardening time for the pumpable slurry is at least 2 hours at a formation temperature of at least 300° F.; A method comprising:
22. 22. The method of claim 21, wherein the target location is at least 500 feet underground.
23. The method of claim 21 , wherein the target locations extend in a substantially vertical direction.
24. 22. The method of claim 21, wherein the target locations extend in a direction that is at an angle of at least 30 degrees from substantially vertical.
25. 22. The method of claim 21, wherein the geothermal target temperature at the target location is at least 400°F and the set time of the pumpable slurry is at least 2 hours.
26. 22. The method of claim 21, wherein the geothermal target temperature at the target location is at least 500°F and the set time of the pumpable slurry is at least 2 hours.
27. 22. The method of claim 21, wherein the pumpable slurry is pumped into the annular space between the wellbore and the casing to displace fluid within the annular space.
28. 28. The method of claim 27, wherein a secondary conduit defining a return space is disposed within the casing, and a second annular space is formed between the casing and the secondary conduit.
29. 30. The method of claim 28, wherein the displacement of fluid includes removing fluid through the return space with a second fluid moving from the second annular space to the return space.
30. 30. The method of any one of claims 21 to 29, wherein the formation includes a plurality of fractures at least partially filled with a high thermal conductivity material, the high thermal conductivity material in the fractures exchanging heat with the high thermal conductivity grout in the wellbore.
31. 31. The method of claim 30, wherein the high thermal conductivity material in the cracks is selected from the group consisting of graphite powder, flake graphite, pyrolytic graphite, desulfurized petroleum coke, graphene, fly ash, copper powder, aluminum nitride, and silicon carbide.
Citation Information
Patent Citations
Heat-transfer cement-based grouting material
CN106810181A
Control system to manage and optimize a geothermal electric generation system from one or more wells that individually produce heat
US20100269501A1
Geothermal well using graphite as solid conductor
US20110232858A1
Thermally conductive grout for geothermal heat pump systems
US20070125274A1
Geothermal grout, methods of making geothermal grout, and methods of use
US20120247766A1